A multiple hydrogen-bonded three-dimensional supramolecular architecture composed of a unique three-fold interlocked anionic Zn(ii)-coordination architecture. Issue 13 (11th March 2020) - Ke, Hua; Chen, Qi-Hua; Liao, Jian-Zhen; Lu, Can-Zhong
Abstract : A multiple hydrogen bonded 3D supramolecular architecture composed of interlocked anionic Zn(ii )-coordination architecture possesses two kinds of distinct cavities in the interlocked positions and between adjacent self-knitting layers respectively. Abstract : An unprecedented three-dimensional multiple hydrogen bonded supramolecular framework containing an interlocked three-fold self-knitting structural topology, which is based on a pseudo graphene-like unweaving monolayer of a Zn(ii )-coordination complex, is obtained via a solvothermal synthesis method. Two different large cavities are generated in this supramolecular architecture. Furthermore, the investigation of the Hirshfeld surface analysis reproduces the results of an X-ray crystal structure analysis and expounds the intermolecular interactions experienced by complexes in a visual manner.